2013
DOI: 10.1128/aem.02644-12
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Rearrangement of Three Different Genetic Determinants into a Conjugative Plasmid Increase Copper Resistance in Pseudomonas syringae

Abstract: We describe the genetic organization of a copper-resistant plasmid containing copG and cusCBA genes in the plant pathogen Pseudomonas syringae. Chromosomal variants of czcCBA and a plasmid variant of cusCBA were present in different P. syringae pathovar strains. Transformation of the copper-sensitive Pseudomonas syringae pv. syringae FF5 strain with copG or cusCBA conferred copper resistance, and quantitative real-time PCR (qRT-PCR) experiments confirmed their induction by copper. Pseudomonas syringae is a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 46 publications
2
39
0
4
Order By: Relevance
“…Other integrated conjugative elements containing Trb conjugal protein loci were also found in RGP26, RGP36, and RGP75, the latter two also containing the copG gene, which encodes a putative metal-transporting P-type AT-Pase, thought to confer copper resistance [20]. Furthermore, the element contained within RGP75 has been sequenced in P. aeruginosa strain NCGM2.S1 previously, as well as having 99% identity with the P. putida sequenced in this study.…”
Section: Genome Analysis Of Xdr St111 Isolatesmentioning
confidence: 53%
“…Other integrated conjugative elements containing Trb conjugal protein loci were also found in RGP26, RGP36, and RGP75, the latter two also containing the copG gene, which encodes a putative metal-transporting P-type AT-Pase, thought to confer copper resistance [20]. Furthermore, the element contained within RGP75 has been sequenced in P. aeruginosa strain NCGM2.S1 previously, as well as having 99% identity with the P. putida sequenced in this study.…”
Section: Genome Analysis Of Xdr St111 Isolatesmentioning
confidence: 53%
“…Partway through copS the two ICEs diverge at a recombination breakpoint with the downstream variable region from Psa NZ45 ICE_Cu being homologous to a set of copper resistance genes found on plasmid pPaCu1 from the divergent (non‐pandemic) Japanese isolate of Psa (J2) (Nakajima et al ., ). This region comprises a putative copper transporting ATPase encoded by copG (Gutiérrez‐Barranquero et al ., ) , cusABC genes involved in the detoxification of monovalent cations, including copper and silver (Mergeay et al ., ; Rensing and Grass, ) and copABCD (Fig. B).…”
Section: Resultsmentioning
confidence: 99%
“…tomato (Lim and Cooksey, 1993) and on the C. metallidurans CH34 pMOL28 and pMOL30 (Monchy et al, 2006). Interestingly, the genetic organization of a copper-resistant conjugative plasmid containing copABCD, copG and cusCBA genes in the plant pathogen Pseudomonas syringae was recently described (Guti errez- Barranquero et al, 2013) and it was shown that copG and cusCBA increased copper resistance in P. syringae. Similarly, in strain B9, the cluster of cop genes on contig 195 also includes copG and features a cusCBAF operon upstream.…”
Section: Discussionmentioning
confidence: 99%